Re-Design Alat Bantu Pengangkut Galon Air Untuk Ibu Rumah Tangga Berbasis Anthropometri - Rusnita, Edit; Mansyur, Syaiful (Universitas Muhammadiyah Sorong, 2026)
MMH activities are still commonly found in our daily activities, such as carrying water gallons. Water gallons are carried not only in offices but also in homes by housewives. Although there are now many commercially available tools to assist in carrying water gallons, the design of these tools still needs improvement. The results of the study show that MMH activities carried out by women, especially housewives, even when using trolley aids, still produce a RULA value of 11. This indicates that immediate improvements are needed in terms of posture when transporting water gallons. Based on this, immediate improvements are needed in the design of existing water gallon transport trolleys in order to reduce the incidence of musculoskeletal disorders (MSDs), especially in women. This study will redesign water gallon transport trolleys based on anthropometry, adjusted to the results of body posture assessments and complaints related to the previous trolley design. Body posture assessments use the RULA and REBA methods to determine the degree of likelihood of MSDs. The Nordic questionnaire will also be given to respondents to find out what complaints housewives have when transporting water gallons using the current water gallon transport trolley. Furthermore, the results of the RULA REBA worksheet and Nordic questionnaire will be used as a basis for redesigning the water transport trolley. The redesign resulted in a proposed design for a water gallon transport trolley that focuses on the anthropometry of housewives.